ARTIKEL REVIEW, PEMANFAATAN TELUR IKAN SEBAGAI PRODUK KONSENTRAT PROTEIN IKAN - Junianto - (Universitas Mataram, 2024)
Fishery product processing industry waste that has the potential to be used into high added value products is fish eggs. The highest nutritional content of fish eggs after water is protein, so they are very suitable for making protein concentrate products. This article aims to review the use of fish eggs as a protein concentrate product. The research method used is a literature study on protein concentrates made from fish eggs, especially commercial fish which are used as raw materials for the processing industry. Literature search using the Google Chrome search engine. The discussion concentrates on the proximate composition of fish eggs, the manufacture of protein concentrate and the proximate composition of fish egg protein concentrate. The data obtained was analyzed in a comparative descriptive manner. Based on the results of the review, it can be stated that fish eggs as a waste product from the fish processing industry can be made or utilized into protein concentrate products. The principle of the manufacturing stages is to remove as much water and fat as possible from the fish eggs. Fish egg protein concentrate products can be applied as complementary foods for baby's breast milk (MP-ASI).